Perceptions and Utilization of Lung Cancer Screening Among Primary Care Physicians. Issue 11 (November 2016) - Raz, Dan J.; Wu, Geena X.; Consunji, Martin; Nelson, Rebecca; Sun, Canlan; Erhunmwunsee, Loretta; Ferrell, Betty; Sun, Virginia; Kim, Jae Y.
ABSTRACT : Introduction : Lung cancer screening (LCS) with low‐dose computed tomography (LDCT) is effective at reducing lung cancer mortality in high‐risk current and former smokers. Despite the fact that screening is recommended by the U.S. Preventative Services Task Force (USPSTF), few eligible patients are screened. We set out to study the barriers to LCS by surveying primary care physicians (PCPs). Methods : We surveyed a randomly selected sample of 1384 eligible PCPs between January and October 2015, using the American Medical Association Physician Masterfile, though surveys sent by mail, fax, and e‐mail. The survey included questions regarding knowledge of LCS guidelines, utilization of LCS over the prior 12 months, and perceptions of barriers to LCS. Training background, years in practice, practice type, and demographics were also collected. Results : The survey response rate was 18%. Responders and nonresponders did not differ by practice or demographic characteristics. Of the respondents, 47% indicated that LCS was recommended by the USPSTF, 52% had referred at least one patient for LDCT, and 12% had referred at least one patient to a LCS program over the prior 12 months. Perceived barriers to LCS included uncertainty regarding ther benefit of LCS, concern regarding insurance coverage, and the harm of LCS. Conclusions : Although LCS is recommended by the USPSTF, LDCT is utilized in a minority of eligible patients, as reported by surveyed PCPs. Approximately half of PCPs are familiar with USPSTF recommendations for LCS and a number of physician barriers to adherence to guidelines exist. Additional study of physician‐ and system‐based interventions to improve adherence to LCS recommendations is needed.